THE IMPACT OF CHANGES IN PUBLIC PROCUREMENT ON THE DEVELOPMENT OF PUBLIC FINANCES IN UKRAINE UNDER THE CONDITIONS OF EUROPEAN INTEGRATION (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. This article examines the transformative effects of public procurement reforms on the development of public finances in Ukraine, especially within the context of the country's ongoing European integration. With Ukraine's strategic pivot towards the European Union, aligning its public procurement policies with EU standards has become imperative. The study meticulously analyzes the legislative changes implemented to harmonize Ukraine's procurement system with the EU's stringent requirements, focusing on transparency, competition, and anti-corruption measures.The purpose of the article. The purpose of the article is to reveal the main features and problems of public procurement in Ukraine in modern conditions and to identify ways to overcome them/Metods. The study employs a comprehensive methodology, incorporating quantitative data analysis and qualitative assessments from various stakeholders, including government officials, procurement professionals, and EU advisors.Results. The article delves into the challenges and limitations faced during the implementation of these reforms. It underscores the necessity for continuous monitoring and adaptation of policies to ensure sustained progress. The transition has also required significant capacity building and training for public officials to effectively manage the new systems and adhere to best practices in procurement. By providing a nuanced understanding of the interplay between procurement reforms and public finance development, the article offers valuable insights for policymakers, economists, and international bodies involved in the reform processes.Conclusiоns. The article posits that while the journey towards fully integrated and efficient public procurement in Ukraine is ongoing, the initial steps have laid a robust foundation for future advancements. Continued commitment to reform and international cooperation is essential for realizing the full potential of these changes in bolstering Ukraine's public finances and overall economic health amidst its European integration efforts.
Keywords: public finance, public procurement